2020
DOI: 10.1080/1061186x.2020.1853759
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on the antiviral activities of chalcones

Abstract: Some viral outbreaks have plagued the world since antiquity, including the most recent COVID-19 pandemic. The continuous spread and emergence of new viral diseases have urged the discovery of novel treatment options that can overcome the limitations of currently marketed antiviral drugs. Chalcones are natural open chain flavonoids that are found in various plants and can be synthesised in labs. Several studies have shown that these small organic molecules exert a number of pharmacological activities, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 106 publications
(249 reference statements)
0
55
0
1
Order By: Relevance
“…A docking study suggested that the antiviral activity of (190) might depend on its strong binding affinity to tobacco mosaic virus coat protein (TMV-CP). There are several other reports on antiviral properties of synthetic chalcone derivatives available in the literature to date, including a few excellent review articles on this topic [108][109][110].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…A docking study suggested that the antiviral activity of (190) might depend on its strong binding affinity to tobacco mosaic virus coat protein (TMV-CP). There are several other reports on antiviral properties of synthetic chalcone derivatives available in the literature to date, including a few excellent review articles on this topic [108][109][110].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Interaction of these flavonoids with ACE2 may also impede the binding of SARS-CoV-2 spike protein and is in line with the anti-viral properties of these compounds [149].The interaction of flavonoids with Mpro, Spike receptor binding domain (Spike-RBD), RNA -dependent RNA polymerase (RdRp or Nsp12), non-structural protein 15 (Nsp15) and the host ACE-2 spike-RBD binding domain have been examined using advanced computation molecular docking techniques. These en-silicoSARS-CoV-2 binding studies indicated that tribuloside, legalon and isosilybin had anti-viral antiinfective properties, warranting further evaluation to determine how effective they are in the inhibition of SARS-CoV-2 infectivity [150].A range of chalcone derivatives have been evaluated using molecular docking methods to assess the effectiveness of these re-purposed compounds on the prevention of the infectivity and replication of SARS-CoV-2 [151][152][153][154][155].…”
Section: A) Anti-viral Properties Of Plant Phytochemicals Against Sars-cov-2 Viral Functionsmentioning
confidence: 99%
“…2 Up to now, chalcones have been postulated for multiple therapeutic effects, especially anticancer, anti-inammatory, antioxidant, antitumor, anti-bacterial, antiviral, and anti-fungal activities. [3][4][5][6][7][8] Moreover, several chalcone-derivatives have been investigated and proved for efficient inhibition of key enzymes responsible for viral replication of SARS-CoV, HIV, HBV, or HCV. 9 The bioactivity of chalcones is undoubtedly based on their structural features, especially the position and the type of substituents in both phenyl rings, such as saturated or unsaturated hydrocarbon groups, halogens atoms, additional aromatic or heteroaromatic rings, bulky cyclopropyl or adamantane domains, as well as hydroxyl, carboxylic or amide groups.…”
Section: Introductionmentioning
confidence: 99%